Transboundary hydropower projects: allocation of competence and cooperation between the federation and its federating units in Switzerland - Chukwuebuka Edum (Frontiers in Climate, 2024)
(i) The Swiss Constitution places cantons (federating units) in charge of managing all water uses. At the same time, it gives the federation decision-making authority over transboundary water uses, including for hydropower purposes. (ii) It further mandates the Federation to consult and consider the concerns and interests of the affected cantons when deciding on transboundary hydropower projects. (iii) Aside from the possibility of intertwining competence between the Federation and cantons on the transboundary hydropower project, the situation creates ambiguity around the obligation to consult between parties on such projects. (iv) Cooperation in good faith in implementing relevant procedural rules of consultation between parties seems to be the most promising approach to finding solutions acceptable to all.